2008
DOI: 10.1103/physrevlett.101.105501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductance of Thin Silicon Nanowires

Abstract: The thermal conductance of individual single crystalline silicon nanowires with diameters less than 30 nm has been measured from 20 to 100 K. The observed thermal conductance shows unusual linear temperature dependence at low temperatures, as opposed to the T3 dependence predicted by the conventional phonon transport model. In contrast to previous models, the present study suggests that phonon-boundary scattering is highly frequency dependent, and ranges from nearly ballistic to completely diffusive, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
308
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(334 citation statements)
references
References 32 publications
23
308
3
Order By: Relevance
“…Measurements of the thermal conductivity of SiNWs were reported by Li et al (2003), who measured thermal conductivities more than two orders of magnitude lower than bulk from VLS-grown nanowires with relatively smooth surfaces of diameters ranging from 22 to 115 nm. More recent works by Chen et al (2008) and Doerk et al (2010) have confirmed these observations and proposed explanations based on phonon-boundary scattering in thin nanowires. Simultaneously, much computational effort has been devoted to the elucidation of heat transport phenomena in very thin SiNW.…”
Section: Heat Conduction In Si Nanowiressupporting
confidence: 60%
See 1 more Smart Citation
“…Measurements of the thermal conductivity of SiNWs were reported by Li et al (2003), who measured thermal conductivities more than two orders of magnitude lower than bulk from VLS-grown nanowires with relatively smooth surfaces of diameters ranging from 22 to 115 nm. More recent works by Chen et al (2008) and Doerk et al (2010) have confirmed these observations and proposed explanations based on phonon-boundary scattering in thin nanowires. Simultaneously, much computational effort has been devoted to the elucidation of heat transport phenomena in very thin SiNW.…”
Section: Heat Conduction In Si Nanowiressupporting
confidence: 60%
“…In particular, silicon nanowires (SiNW) have shown promise as components for nanoelectronic devices, thereby spurring extensive research into synthesis processes (Cui et al, 2001;Hochbaum et al, 2008) and fundamental thermal and electrical properties Shi et al, 2003;Chen et al, 2008;Doerk et al, 2010). In particular, these investigations have revealed a strong dependence of thermal conductivity on size and surface morphology (Cui et al, 2001).…”
Section: Heat Conduction In Si Nanowiresmentioning
confidence: 99%
“…Following the microfabricated structures mentioned above, significant progress has been made in investigating the thermal conductivity in various one dimensional structures, such as SiNWs, [133][134][135] CNTs and boron nitride nanotubes, 44 75 in Ge-Si core-shell ultrathin NWs. 141,142 The development of suspended microfabricated structures for thermal properties measurement has paved the way for many significant studies in understanding the fundamental thermal transport at nanoscale.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…141,142 The development of suspended microfabricated structures for thermal properties measurement has paved the way for many significant studies in understanding the fundamental thermal transport at nanoscale. 44,71,133 Recently, by taking advantage of their advances in nanofabrication, Li and Thong managed to fabricate the MEMS in the size of 8 inches, with more than 600 devices integrated in one single wafer (insert in Fig. 11).…”
Section: A 1d Nanostructuresmentioning
confidence: 99%
“…However, the NWs easily reach temperatures well above room temperature under the excitation with a focused laser beam; therefore, values of the thermal conductivity at temperatures over 320 K are necessary for solving the heat transfer in NWs. The limitation of the thermal conductivity of NWs is due to the phonon boundary scattering, therefore, the thermal conductivity is decreased when reducing the NW diameter, but also for rough surface NWs [9, 44,46,47]. Keeping all these considerations in mind, we have proceeded to calculate the thermal conductivity of Si NWs at temperatures above 320 K. For this, we have used a modified Callaway-Holland formalism [48], and we checked the model by the satisfactory fitting to the available experimental data on both smooth and rough NWs; for more details, see Anaya et al [48].…”
Section: The Thermal Conductivity Of Nwsmentioning
confidence: 99%